Pelatihan Microsoft Office Excel untuk Penyusunan Laporan Keuangan Organisasi Siswa SMA/SMK Se-Kecamatan Mantup: Preparing Financial Reports for Senior High School Student Organisations in Mantup District: Microsoft Office Excel Training - Amalliyah, Nor (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Effective and efficient financial management is one of the keys to the success of an organization. Efforts to increase the effectiveness of financial management are by utilizing information technology, namely Microsoft Office Excel. So far, financial management of student organizations has been done manually and has not been properly computerized. This happens because students find it difficult to operate Microsoft Office Excel. So it is necessary to conduct Microsoft Office Excel training for high school/vocational high school students in preparing financial reports. The training is aimed at high school / vocational high school students in the Mantup District Area who are actively involved in organizations at their schools. The purpose of this training is to provide students with knowledge about the basics of using Microsoft Office Excel so that they can apply their knowledge to prepare financial reports effectively. The activity was carried out in 3 stages, namely the planning, implementation, and evaluation stages. The results showed that participants gave a positive response to the training that had been carried out. Participants stated that Microsoft Office Excel training was very useful because it could improve participants' knowledge and skills in preparing financial reports for the organizations they attended at their respective schools.